Analisis Pengaruh Metode Camel Terhadap Tingkat Kesehatan Bank Syariah Mandiri Periode 2015-2017 - Inngamul Wafi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Bank Syariah Mandiri is a sharia commercial bank that has implemented CAMEL analysis as a benchmark for health. So this research aims to see whether there is an influence of the camel method on the health level of Bank Syarah Mandiri for the 2015-2017 period. This research uses a combination research method with quantitative analysis using multiple linear regression analysis techniques to predict changes in a variable caused by other variables. The sample used is the quarterly financial ratios of Bank Syariah Mandiri for the 2015-2017 period. The results of this research indicate that hypothesis 1 obtained a CAR ratio, namely tcount as big as 4,729 > 2,776, meaning Capital has a positive effect on the bank's health level. Hypothesis 2 obtained KAP ratio obtained tcount -0.251 < 2.776 and PPAP obtains tcount 0.309 < 2.776, meaning Asset Quality has no positive or negative effect on the bank's health level. Hypothesis 3 shows that the NPM value obtained a significant value of 0.380 > 0.05 and tcount 0.987 < 2.776, meaning that management has no positive or negative influence on the bank's health level. Hypothesis 4 shows that the ROA ratio obtains a significant value of 0.003 < 0.05 and tcount 3,300 > 2.776 and the BOPO ratio has a significant value of 0.014 < 0.05 and tcount 2.908 > 2.776, meaning Earning has a positive effect on the bank's health level. Hypothesis 5 shows that FDR has a significant value of 0.004 < 0.05 and tcount -3.611 > -2.776, meaning, Likuidity has a negative effect on the bank's health level.